Centrifugação do líquido ascítico para diagnóstico etiológico de peritonite bacteriana espontânea - Yamashiro, Fabio da Silva [UNESP] (2015)
Spontaneous bacterial peritonitis (SBP) are common infectious complications in patients with liver cirrhosis and ascites. The diagnosis is made by collecting ascites and counting nuclear polymorph (PMN). Values above 250 PMN / mm³ are sufficient for the start of empirical treatment with antibiotics. The SBP are usually caused by Gram-negative enterobacteria, however currently observed changes in the profile of the pathogens, an increase of Gram-positive bacteria and emerging multi-resistant strains. The sensitivity of ascitic fluid bedside seeded in culture bottles culture is about only 20 to 40%. The main objective was to evaluate the positive ascites cultures using larger volume (50ml) centrifugation and seeding the liquid in the laboratory. The secondary objective was to evaluate the correlation between C-reactive protein levels (CRP) in the blood and in the ascites PMN of patients being treated for PBE. The observational study of 51 cases of SBP in adults comparing results obtained by analysis of the amount of PMN in ascites, serum CRP, cultures at the bedside and cultures obtained after centrifugation. In the sample 90% of the cases were male, being the main cause of cirrhosis the alcohol abuse (55%). The average value of PCR in diagnosis was 10.5 +/- 8.23. The positivity of culture at the bedside was 31%, but using centrifugation this rate increased to 69%. There was also a good correlation between the serum CRP levels in ascites and PMN (R = 0.505, P <0.001). The area ratio obtained under the curve of 0.9545 to 0.8677 to 1.041 confidence interval and P <0.001, with the cutoff delta PCR for correlation with treatment response to a decrease of at least 24% the value of the initial PCR. Observed in our study cases antibiotic resistance, Escherichia coli resistant trimethropim sulfamethoxazole and levofloxacin used for the primary and secondary prophylaxis EBP frame or the treatment thereof. The collection method associated with ...